Oddie's adventure - Haq, Roohi (Karachi : Paramount books, 2015)
"Oddie's Adventure" likely follows the journey of Oddie, a character who appears to be a donkey with a flower on its head. The story seems to take place at night under a full moon, possibly involving a farm or rural setting with a barn. Oddie might be embarking on some kind of quest or exploration in this nighttime landscape.
Location: 3B
Keywords: Oddie's adventure book